Human epidermal growth factor receptor 2/neu and the clinico-pathological profile in breast cancer: an observational study at a tertiary care hospital in Central India - Shukla, Shikha; Ansari, Fahad (International Surgery Journal, 2021)
Background: Breast cancer is the most commonly occurring cancer in women and the second most common cancer overall. Owing to a unique pattern of presentation in terms of clinical and biological features, finding their mutual association may be important and may help predict prognosis. HER2 (human epidermal growth factor receptor 2)/neu is one such important immunohistochemical factor that is considered to be more prevalent amongst Indians and therefore makes up for an emerging area for studies. The study aimed to assess the patients of breast carcinoma in terms of their HER2/neu statuses and find out their association with clinical parameters. Methods: This was a prospective comparative study conducted in department of surgery, Hamidia hospital, Bhopal, India, with a total duration of 1 year between November 2018 to September 2019 including a total of 98 consecutive in house breast carcinoma patients. Results: A total of 98 breast cancer patients were tested for HER-2/neu gene presence. Of these 25 (25.5%) samples tested positive and 73 (7.48%) tested negative. A comparison of the two groups revealed that none of the clinic-pathological factors tested were found to have a statistically significant association with the HER2/neu status. Conclusions: It appeared that there is no defining factor in terms of clinic-pathological presentation that helps to separate significantly HER-2/neu positive with HER-2/neu negative cases with breast cancer. Still, immune-histochemical marker analysis should be an integral part of the overall work up of the breast cancer patients because of its both prognostic and therapeutic application and significance.